E-waste management in higher education institutions: insights and policy recommendations - Galleto Jr., Fredelino A.; Dayaday, Maricel G.; De Leon, Frediezel G. (International Journal of Public Health Science (IJPHS), 2025)
Electronic waste disposal is a primary concern both on a national and global spectrum. The increased usage of information and communication technology and electronic devices among higher education institutions (HEIs) contributes to the annual generation of e-waste. HEIs are called to implement a sustainable scheme to curtail the environmental and public health threats brought by e-waste. Against this background, the recycling strategies of HEIs for discarded electronics were examined and evaluated as to its effectiveness and used as basis to develop policy recommendations for e-waste management. The interventions developed were met with general approval and positive response. The innovative products were perceived to be useful in serving their new purposes and reducing the problems of e-waste in HEIs. These findings provide valuable input for HEIs seeking to enhance their e-waste recycling practices. Existing legislation concerning e-waste was looked into, and policy recommendations that encouraged cooperation and shared accountability among key players and stakeholders were drawn up.